Preserving the Past: The Role of the Peruvian Adventist Union University in the Management of the Unión Ñaña Archaeological Zone - Padilla Yabar, Araselly (2025)
The Union Ñaña Archaeological Zone is located on La Parra Hill, in Lima, Peru. The Peruvian Union University (UPeU) led the cultural management efforts in 1993 and 1994 to protect the archaeological site from urban expansion and illegal land trafficking, achieving its designation and delimitation as a National Cultural Heritage site. Afterward, they assessed its conservation, controlled the expansion of human settlements, and carried out cultural mediation efforts. This article presents the cultural management experience of the Union Ñaña Archaeological Zone by UPeU, using a qualitative methodological approach, including interviews with key stakeholders and field visits. We examine category values and heritage subjects, highlighting their importance for the community and academia. The study concludes that UPeU's leadership was essential in preserving the site, but greater state involvement is needed for its long-term sustainability.